La importancia de lo psico-afectivo en el ámbito de la educación (Memorias Sifored - Encuentros Educación UAN, 2023)
In the field of education, we face a fundamental challenge that impacts the development of students. This problem has gained considerable strength over the years since education is not only about academic knowledge but must also consider mental and emotional health. The objective is to analyze the importance of psycho-affective in education and how it influences the learningand well-being of students. To achieve this objective, a methodology of research and observation of pedagogical practices in different educational environments will be used. The results try to integrate the importance of psycho-affective in education and highlight how these results can contribute to a much healthier educational environment and the development of socio-emotional skills in students.
Keywords: education; emotional education; psycho-affective; mental health and academic knowledge